2020
DOI: 10.1186/s12889-020-08525-8
|View full text |Cite
|
Sign up to set email alerts
|

Household presentation of acute gastroenteritis in a primary care sentinel network: retrospective database studies

Abstract: Background: Acute gastroenteritis (AGE) is a highly transmissible condition spreading rapidly between individuals and within households. Rotavirus vaccination was introduced in the UK in 2013. The study objectives were to investigate how acute gastroenteritis incidence changed over 25 years and household incidence of AGE since 2013. Methods: Repeated cross-sectional study of Royal College of General Practitioners Research and Surveillance Centre network. We used a negative binomial model to report incidence ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…Studies have shown male gender is a risk factor for contracting AGE 201,202 . This is in line with our results, which reports a higher prevalence of SaV in boys (10.1%) than girls (8.6%).…”
Section: Discussionsupporting
confidence: 93%
“…Studies have shown male gender is a risk factor for contracting AGE 201,202 . This is in line with our results, which reports a higher prevalence of SaV in boys (10.1%) than girls (8.6%).…”
Section: Discussionsupporting
confidence: 93%
“…Other variables included: age; sex; socioeconomic status using the index of multiple deprivation (IMD), based on lower super output area (LSOA) — a geographical subunit with a minimum population of 1000 — divided into quintiles; 13 ethnicity divided into white, Asian, black, mixed, and others; 14 and household size; determined using a pseudonymised household key based on identical address, this has been used in other studies. 10 , 15 , 16 smoking status (comparing current, ex- and non-smokers); obesity (using the World Health Organization categorisation of overweight [body mass index {BMI} = 25–29 kg/m 2 ]; obese [BMI = 30–34 kg/m 2 ]; and severely obese [BMI≥35 kg/m 2 ]; and population density (based on ONS locality data). 17 The highest population density was in ‘conurbations’, medium levels in ‘city and town’, and lowest density in ‘rural areas’.…”
Section: Methodsmentioning
confidence: 99%
“…household size; determined using a pseudonymised household key based on identical address, this has been used in other studies. 10 , 15 , 16 …”
Section: Methodsmentioning
confidence: 99%
“…Demographic and personal characteristics included gender, age, and ethnicity divided into white, Asian, Black, mixed and other, using an established ontology, 20 household size (1, 2–4,5–8 and 9 + ), 15 , 21 , 22 and socioeconomic status as determined by the Index of Multiple Deprivation (IMD). 23 We used the following body mass index (BMI) categories: (1) under weight and normal weight were grouped into “normal” (BMI<25 kg/m 2 ); (2) overweight or pre-obese (BMI 25–29 kg/m 2 ); (3) obese class I (BMI 30–34 kg/m 2 ); and (4) obese class II and III (BMI ≥35 kg/m 2 ).…”
Section: Methodsmentioning
confidence: 99%